Quantitative Genetics of Feed-Efficiency-Related Traits for the Pacific Whiteleg Shrimp Penaeus vannamei in a Plant-Based Diet Environment - Ping Dai; Xiangyan Zhu; Sheng Luan; Juan Sui; Xianhong Meng; Jiawang Cao; Jian Tan; Jie Kong (Biology)
Selecting shrimp strains that perform well on a plant-based diet holds promise for solving the fishmeal (FM) shortage issue, with genetic improvement of feed efficiency (FE) being a key focus. This study compared a plant-based (fishmeal-free) diet with a 25% FM diet for the Pacific whiteleg shrimp (Penaeus vannamei) to determine whether the FE-related traits, including residual feed intake (RFI), average daily weight gain (ADG), and daily feed intake (DFI), exhibit diet-specific genetic variations and genotype-by-diet (genotype × diet) interactions. Results showed that RFI was significantly higher under the plant-based diet treatment compared to the FM-based diet treatment (0.0049 g/d vs. –0.0045 g/d, p < 0.001), while ADG was notably lower (0.043 g/d vs. 0.110 g/d, p < 0.001), indicating that a plant-based diet may lead to reduced yields and impact the profitability of shrimp culture. In the case of being unable to estimate common environmental effects, the heritability estimates of RFI under the plant-based and FM-based diets were 0.743 ± 0.157 and 0.440 ± 0.125, respectively, and those of ADG and DFI ranged from 0.314 ± 0.121 to 0.947 ± 0.158. Genetic correlations between diets for RFI and DFI were 0.646 ± 0.162 and 0.549 ± 0.163, respectively, suggesting a degree of genotype × diet interactions. In contrast, the genetic correlation between diets for ADG was only 0.296 ± 0.259, indicating a strong genotype × diet interaction. These findings highlight the importance of considering selective breeding for improved feed efficiency in a plant-based diet environment.